A novel assessment of the role of the methyl radical and water formation channel in the CH 3 OH + H reaction - Sanches-Neto, Flávio O.; Coutinho, Nayara D.; Carvalho-Silva, Valter H. (Physical chemistry chemical physics : PCCP, 2017)
A number of experimental and theoretical papers accounted almost exclusively for two channels in the reaction of atomic hydrogen with methanol: H-abstraction from the methyl (R1) and hydroxyl (R2) functional groups. Recently, several astrochemical studies claimed the importance of another channel for this reaction, which is crucial for kinetic simulations related to the abundance of molecular constituents in planetary atmospheres: methyl radical and water formation (R3 channel). Here, motivated by the lack of and uncertainties about the experimental and theoretical kinetic rate constants for the third channel, we developed first-principles Car–Parrinello molecular dynamics thermalized at two significant temperatures – 300 and 2500 K. Furthermore, the kinetic rate constant of all three channels was calculated using a high-level deformed -transition state theory ( d -TST) at a benchmark electronic structure level. d -TST is shown to be suitable for describing the overall rate constant for the CH 3 OH + H reaction (an archetype of the moderate tunnelling regime) with the precision required for practical applications. Considering the experimental ratios at 1000 K, k R1 / k R2 ≈ 0.84 and k R1 / k R3 ≈ 15–40, we provided a better estimate when compared with previous theoretical work: 7.47 and 637, respectively. The combination of these procedures explicitly demonstrates the role of the third channel in a significant range of temperatures and indicates its importance considering the thermodynamic control to estimate methyl radical and water formation. We expect that these results can help to shed new light on the fundamental kinetic rate equations for the CH 3 OH + H reaction.